2022
DOI: 10.1016/j.psychres.2021.114353
|View full text |Cite
|
Sign up to set email alerts
|

Risk of post-traumatic stress symptoms in hospitalized and non-hospitalized COVID-19 recovered patients. A cross-sectional study

Abstract: High rates of post-traumatic stress disorder (PTSD) symptoms have been found among patients with more severe COVID-19-related symptoms, and hospitalization is generally recognized as a risk factor for developing PTSD. Furthermore, other personality characteristics may increase the risk of developing post-traumatic stress symptoms following a COVID-19 infection. This study aimed to assess personality traits, alexithymia, dissociation, anxiety, and depression in patients who have recovered from COVID-19 and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 45 publications
5
35
0
Order By: Relevance
“…Another interesting approach would be to assess the sense of gains and losses resulting from the experience of pandemic relative to the baseline level of optimism, hope, and sense of meaning in life. It would also be interesting to further discuss the impact of the COVID-19 pandemic on the mental health and sense of changes in life in more fragile populations, such as pregnant women and patients recovered from more severe COVID-19 disease [ 88 , 89 ], due to their specific vulnerability to the negative impact of pandemic on their lives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting approach would be to assess the sense of gains and losses resulting from the experience of pandemic relative to the baseline level of optimism, hope, and sense of meaning in life. It would also be interesting to further discuss the impact of the COVID-19 pandemic on the mental health and sense of changes in life in more fragile populations, such as pregnant women and patients recovered from more severe COVID-19 disease [ 88 , 89 ], due to their specific vulnerability to the negative impact of pandemic on their lives.…”
Section: Discussionmentioning
confidence: 99%
“…In future research, more detailed information concerning participant lifestyles and changes in their habits (e.g., diet, participation in sport, and addictive behaviours) should be taken into consideration to better comprehend the complex underpinnings of subjective evaluation of one’s own life during the pandemic [ 90 ]. Moreover, comparisons between hospitalized and non-hospitalized COVID-19 recovered patients with regard to their sense of gains and losses during lockdown is another interesting area of future study [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…These neurological disorders are attributed to endothelial injury and microangiopathy, which was described in brain biopsies of severe form of COVID-19. 39 Also, severity of condition and PTSD could be co-factor in neuropsychiatric persistence symptoms, 40 in children it seems similar to the late Kawasaki syndrome that was reported after COVID-19. 41 …”
Section: Discussionmentioning
confidence: 61%
“…For example, we did not have access to the results of pulmonary function tests and therefore could not ascertain disease severity. Studies have reported that long COVID-19 symptoms are more likely to occur in patients who experienced more severe COVID-19 9 12 25. In Japan, patients with COVID-19 with mild disease are usually treated at home or in residential care facilities without medical care, and only those with severe symptoms are hospitalised.…”
Section: Discussionmentioning
confidence: 99%